Antibacterial Activity of Germacrone Sesquiterpene from Curcuma Xanthorrhiza Rhizomes - Diastuti, Hartiwi; Syah, Yana Maolana; Juliawaty, Lia Dewi; Singgih, Marlia (UNIVERSITAS SEBELAS MARET (UNS), 2016)
The aim of this research was to isolate and indentify the terpenoid compound from Curcuma xanthorrhiza rhizomes and its antibacterial activity. Isolation was carried out by using vacuum liquid chromatography and centrifugal chromatography. The structure was determined by NMR spectroscopy (1H-NMR, 13C-NMR 1D and 2D), then compare with data from literatures. Antibacterial test was carried out by using microdillution methods and evaluated against eight bacteria. They are Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Enterobacter aerogenes, Pseudomonas aeruginosa, Salmonella typhi, Shigella dysentriae and Vibrio cholerae. The result showed that the isolate was a white crystal which was indetified as germacron-type sesquiterpene. Germacron have highest activity againts P. aeruginosa, MIC 15.6 µg/mL and MBC 31.2 µg/mL.